The Rise of the House of Egibi: Nabû-aḫḫē-iddina - van Driel, G. (1985)
1987; 1. Backgrounds; 2. Nabû-aḫḫē-iddina and the family business; 3. Nabû-aḫḫē-iddina's career as scribe and judge; 4. The Neriglissar connection; 5. The bankruptcy of Nabû-apal-iddina Šanašišu ; 6. Property; 7. The family.